ANALISIS KEMAMPUAN MENYELESAIKAN SOAL GEOMETRI POKOK BAHASAN BANGUN RUANG BERDASARKAN LEVEL VAN HIELE - Cahyo, Rahmad Dwi; Sunardi, S; Yudianto, Erfan (Department of Mathematics Education , University of Jember, 2018)
Abstract. Problem solving skill is very necessary in the field of mathematics, for it is necessary to do the exercises so that the problem solving abilities are increased, one type of problem solving is IDEAL which consists of the stages of identifying, define, explore, act and look. The aim of this research was to determine the ability to solve geometry problems based on van Hiele's level. The test used in this research consisted of two test packages. The first test is to determine the level of van Hiele students and the second test is the geometric subject. The results of the first test show that the van Hiele level of students is at the level of previsualization, 0, 0-1, 1, 1-2, and 2. The second test is given to students at levels 0, 1, and 2. The results of the study show that each student is able to write complete information and can define the objectives by writing down the questions. In writing problem solving strategies and in implementing strategies students experience the tendency to make the wrong solution strategies. At the evaluation stage students have not been able to arrange solutions with different way. Keywords: IDEAL, problem solving, van Hiele, solid figure